2017
DOI: 10.1186/s12985-017-0784-7
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide inhibits EBV reactivation and promotes cell death in EBV-positive lymphoma cells

Abstract: BackgroundEpstein-Barr Virus (EBV) is associated with hematopoietic malignancies, such as Burkitt’s lymphoma, post-transplantation lymphoproliferative disorder, and diffuse large B-cell lymphoma. The current approach for EBV-associated lymphoma involves chemotherapy to eradicate cancer cells, however, normal cells may be injured and organ dysfunction may occur with currently employed regimens. This research is focused on employing arsenic trioxide (ATO) as EBV-specific cancer therapy takes advantage of the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…Particularly, As 2 O 3 exposure significantly inhibits growth of human T-cell leukemia virus-infected T-cell lines through induction of apoptosis and cell cycle arrest ( Ishitsuka et al, 2000 ). Similarly, As administration was also shown to inhibit Epstein-Barr Virus replication and stimulates cell death in EBV-positive cells ( Yin et al, 2017 ). Due to the observed effects of As exposure on viral agents of leukemia, As and IFN-α is widely used as an antileukemic agent ( Hachiman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, As 2 O 3 exposure significantly inhibits growth of human T-cell leukemia virus-infected T-cell lines through induction of apoptosis and cell cycle arrest ( Ishitsuka et al, 2000 ). Similarly, As administration was also shown to inhibit Epstein-Barr Virus replication and stimulates cell death in EBV-positive cells ( Yin et al, 2017 ). Due to the observed effects of As exposure on viral agents of leukemia, As and IFN-α is widely used as an antileukemic agent ( Hachiman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators have studied the impact of arsenicals on EBV gene expression [ 7 , 8 , 9 , 28 ]. Sides et al reported activation of Zta and BMRF1 RNA expression in epithelial cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al studied EBV-positive lymphoma cell lines treated with As 2 O 3 at nanomolar concentrations for three days or longer. They reported decreased cell viability and reduced expression of Zta and BMRF1 [ 9 ]. Our results parallel those in the previous reports in some regards but differ in others, possibly reflecting differences in particular cell lines studied or in the duration of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They conclude that their results provide evidence for the impact of microenvironment on EBV-carrying DLBCL cells and might have therapeutic implications. Yin et al [ 14 ] are also able to promote cell death in EBV-positive cells in vitro, by using arsenic trioxide (ATO). EBV spontaneous reactivation starts as early as 6 h after re-suspending EBV-positive Mutu cells in RPMI media in the absence of ATO; however, this does not occur in Mutu cells cultured with ATO.…”
Section: Biology Of Lymphomamentioning
confidence: 99%